2002
DOI: 10.1046/j.1365-277x.2002.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the suitability and accessibility of catering practices to inpatients from minority ethnic groups in Brent

Abstract: Improvements could be made to improve accessibility and improve suitability of meal choices to inpatients from minority ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Despite the much-published literature on patient satisfaction, malnutrition remains a common, recurring problem and a challenge worldwide. If inpatients are malnourished, and if meals provided to them are unacceptable, then food may be wasted, which is a weakness (Hartley and Hamid, 2002; Edwards and Hartwell, 2006). Hospital foodservice could reform eating habits after discharge; therefore, it can be regarded as an educational tool for preventing malnutrition.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Despite the much-published literature on patient satisfaction, malnutrition remains a common, recurring problem and a challenge worldwide. If inpatients are malnourished, and if meals provided to them are unacceptable, then food may be wasted, which is a weakness (Hartley and Hamid, 2002; Edwards and Hartwell, 2006). Hospital foodservice could reform eating habits after discharge; therefore, it can be regarded as an educational tool for preventing malnutrition.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In recent years, despite all the attempts to modernize food services, previous studies showed that hospital food services remain to be a widespread problem all over the world (Hartley & Hamid, 2002;Kondrup et al, 2002). For instance, it has been stated that almost half of the patients treated in all the US hospitals faces with malnutrition problem (Hartwell & Edwards, 2003;Wissing, Lennernas, Ek, & Unosson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Malnourished patients admitted to public hospitals and malnutrition perpetuated during hospitalisation could indicate a problem regarding South African hospital foodservice provision (Barker et al, 2011). In total, 40 per cent of hospitalised patients are malnourished, and culturally unacceptable meals are wasted (Hartley and Hamid, 2002). Food wastage is attributed to poor foodservice (Edwards, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%